Chang'E-1 observations of pickup ions near the Moon under different interplanetary magnetic field conditions - Zhong, J.; Xie, L.; Zhang, H.; Li, J. X.; Pu, Z. Y.; Nowada, M.; Wang, X. D.; Wang, X. Y.; Parks, G. K.; Zong, Q. G.; Fu, S. Y.; Guo, R. L.; et al. (Planetary and Space Science, 2013)
Detailed features of the near-Moon pickup ions under different interplanetary magnetic field (IMF) conditions are investigated using data obtained from the solar wind ion detector (SWID-B) onboard Chang'E-1. In the event studied, Chang'E-1 was on a noon-midnight meridian orbit and the field-of-view of the SWID-B was in the satellite orbital plane. The observations show that the pickup energy detected depends not only on where these particles are detected but also on their incident angles. As the spacecraft moved into the wake from the South Pole along the midnight meridian, wider incident angle distributions were measured. When IMF B-x was significant, the pickup ions had a strong velocity component parallel to the magnetic field, and the efficiency of acceleration was reduced when the IMF B-y decreased. The back tracking calculations show that the possible source of the pickup ions is solar wind ions scattered/reflected on the lunar surface in a wide area over the dayside of the Moon, from both magnetic and nonmagnetic anomaly regions. A three dimensional analysis performed on the asymmetric properties of the pick-up ions can explain most of the particle behavior observed near the Moon under different IMF conditions. (C) 2013 Elsevier Ltd. All rights reserved. http://gateway.webofknowledge.com/gateway/Gateway.cgi?GWVersion=2&SrcApp=PARTNER_APP&SrcAuth=LinksAMR&KeyUT=WOS:000318464600005&DestLinkType=FullRecord&DestApp=ALL_WOS&UsrCustomerID=8e1609b174ce4e31116a60747a720701 Astronomy & Astrophysics SCI(E) EI 1 ARTICLE 1 56-63 79-80